2019
DOI: 10.1242/jeb.208637
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of the dive response in trained harbour porpoises(Phocoena phocoena)

Abstract: Pronounced dive responses through peripheral vasoconstriction and bradycardia enable prolonged apnoea in marine mammals. For most vertebrates, the dive response is initiated upon face immersion, but little is known about the physical drivers of diving and surfacing heart rate in cetaceans whose faces are always mostly submerged. Using two trained harbour porpoises instrumented with an ECG-measuring sound-and-movement tag (DTAG-3), we investigated the initiation and progression of bradycardia and tachycardia du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…In addition, the pre-apnea and diving f H 's were within the range of those reported in previous studies in conditioned bottlenose dolphins (Noren et al, 2004;Fahlman et al, 2019bFahlman et al, , 2020b, and did not vary depending on the type of breath-hold (Figure 1). While the f H -response during the breath-hold in the current study is similar to that reported in the harbor porpoise, the pre-dive f H varied considerably in the harbor porpoise (Elmegaard et al, 2016(Elmegaard et al, , 2019. It is possible that a non-random design, where the animal anticipated the task beforehand resulted in changes in the breathing frequency or tidal volume, which are known to alter f H (Cauture et al, 2019;Fahlman et al, 2019bFahlman et al, , 2020b).…”
Section: Evidence For Conditioned Control Of Heart Ratesupporting
confidence: 69%
See 1 more Smart Citation
“…In addition, the pre-apnea and diving f H 's were within the range of those reported in previous studies in conditioned bottlenose dolphins (Noren et al, 2004;Fahlman et al, 2019bFahlman et al, , 2020b, and did not vary depending on the type of breath-hold (Figure 1). While the f H -response during the breath-hold in the current study is similar to that reported in the harbor porpoise, the pre-dive f H varied considerably in the harbor porpoise (Elmegaard et al, 2016(Elmegaard et al, , 2019. It is possible that a non-random design, where the animal anticipated the task beforehand resulted in changes in the breathing frequency or tidal volume, which are known to alter f H (Cauture et al, 2019;Fahlman et al, 2019bFahlman et al, , 2020b).…”
Section: Evidence For Conditioned Control Of Heart Ratesupporting
confidence: 69%
“…While it is clear that the dive response is exhibited by all vertebrates studied and that the response is heritable, its actual role and regulation within and between species is debated (Mottishaw et al, 1999;Fahlman et al, 2011;Ponganis, 2011;Ponganis et al, 2017;Parkes, 2019). A number of factors such a facial immersion (in humans), breathing frequency, tidal volume, age, blood O 2 and CO 2 tension, blood pressure, and emotional state may explain the large variability within and between individuals (Irving, 1963;Harrison et al, 1972;Lin et al, 1972;Jones et al, 1973;Moore et al, 1973;Angell-James et al, 1978Openshaw and Woodroof, 1978;Blix, 1987;Bernardi et al, 1989;Thompson and Fedak, 1993;Castellini et al, 1994a,b;Andrews et al, 2000;Fahlman et al, 2011;Elmegaard et al, 2016Elmegaard et al, , 2019Kaczmarek et al, 2018;Cauture et al, 2019). In addition, previous studies have suggested that at least some marine mammals can be conditioned to alter the f H response depending on anticipation (Elmegaard et al, 2016;Kaczmarek et al, 2018), possibly due to suprabulbar or cortical influences Jones, 1982, 1997;Panneton, 2013).…”
Section: Evidence For Conditioned Control Of Heart Ratementioning
confidence: 99%
“…5. In the plot, we also included published data for the harbor porpoise (Phocoena phocoena), the adult beluga whale (Delphinapterus leucas) and gray whale (Eschrichtius robustus) (Bickett et al, 2019;Elmegaard et al, 2019;Ponganis and Kooyman, 1999;Wahrenbrock et al, 1974). The regression for the cetaceans was: f H =24.8+11.9f R (Fig.…”
Section: Relationship Between F R and F Hmentioning
confidence: 99%
“…By using RSA correction, comparisons within and between species and activity states (inactive, swimming, diving) could be made and be Data for bottlenose dolphin, beluga whale, false killer whale, pilot whale and killer whale are from the present study. Data for harbor porpoise (Phocoena phocoena) and gray whale (Eschrichtius robustus), and additional data for the killer whale, pilot whale and adult beluga whale are from previous studies (Bickett et al, 2019;Elmegaard et al, 2019;Ponganis and Kooyman, 1999;Wahrenbrock et al, 1974). The regression for the cetacean data was:…”
Section: Changes In Co During Rsa Are Made By Variation In Both F H Amentioning
confidence: 99%
“…The elastic tissue network that surrounds the entire MESs and extends into the cartilaginous rings may serve to maintain the lumen of the terminal bronchioles open during explosive ventilation, preventing obstruction of the airways. The mechanisms by which MESs are regulated by the visceral nervous system are not known, and here we also note that, at least in some species, specific respiratory responses to diving may be under somatic control (Elmegaard et al, 2019). In this study, we describe the presence of NFs in the terminal portion of the lung of bottlenose and striped dolphins.…”
Section: Discussionmentioning
confidence: 73%